Case Report: Immune Checkpoint Blockade Plus Interferon-Γ Add-On Antifungal Therapy in the Treatment of Refractory Covid-Associated Pulmonary Aspergillosis and Cerebral Mucormycosis - Serris, Alexandra; Ouedrani, Amani; Uhel, Fabrice; Gazzano, Marianne; Bedarida, Vincent; Rouzaud, Claire; Bougnoux, Marie-Elisabeth; Raphalen, Jean-Herlé; Poirée, Sylvain; Lambotte, Olivier; Martin-Blondel, Guillaume; Lanternier, Fanny (Frontiers in Immunology, 2022)
Invasive fungal diseases (IFD) still cause substantial morbidity and mortality, and new therapeutic approaches are urgently needed. Recent data suggest a benefit of checkpoint inhibitors (ICI). We report the case of a diabetic patient with refractory IFD following a SARSCoV-2 infection treated by ICI and interferon-gamma associated with antifungal treatment.